Quality of Life Assessment in Patients with Multiple Sclerosis Receiving Interferon Beta-1a: A Comparative Longitudinal Study of Avonex and Its Biosimilar CinnoVex. (9th August 2012) - Abolfazli, R.; Hosseini, A.; Gholami, Kh.; Javadi, M. R.; Torkamandi, H.; Emami, S.
Abstract : Background . Multiple sclerosis (MS) is an autoimmune inflammatory disease of central nervous system (CNS). MS affects quality of Life (QOL) due to physical disability and other associated problems. Disease-modifying agents like interferon beta (IFNB) have been widely utilized in this patient population; however, their frequency, route of administration, side effects, high cost, and also the question of whether they are truly beneficial for longer-term outcomes and QOL need to be further investigated. Objectives . To assess QOL in patients with multiple sclerosis receiving interferon beta-1a (Avonex or CinnoVex) and in order to compare QOL in groups receiving Avonex and CinnoVex, respectively, also, to evaluate whether the more cost-effective biosimilar form of IFNB (CinnoVex) has the same effect on QOL and can be substituted for Avonex. Methods . We conducted a 30-month, nonrandomized longitudinal study and recruited a total of 92 patients diagnosed with relapsing-remitting MS. The patients were distributed in Avonex and CinnoVex groups with 46 patients in each group. Quality of life was assessed by means of MSQOL-54 questionnaire, four times a year, at baseline and at months 4, 8, and 12 of the study. Results . Mean age ± SD was 30.5 ± 8.9 and 32.3 ± 9.0 years in Avonex and CinnoVex groups, respectively, and P value of gender was different ( P value : 0.036). The physical health composite scores were 61.8 and 59.8 ( P values 0.677 and 0.884) for Avonex and CinnoVex groups, in that order. The results of the study revealed no significant difference between the two groups with regard to physical health, health perception, energy, and role limitations due to physical problems, pain, sexual and social function, and physical health distress scores. Further, interferon therapy did not significantly impact patients' QOL after a year of treatment with either Avonex or CinnoVex. Conclusions . According to the present study, treatment with IFNB (Avonex or CinnoVex) did not affect QOL during a year of therapy. Further studies with longer follow-up periods are required to assess the value of interferons on long-term outcomes and patient's QOL.